Incremental dynamic based fragility assessment of reinforced concrete structures: Stationary vs. non-stationary artificial ground motions. Issue 103 (December 2017) - Basone, Francesco; Cavaleri, Liborio; Di Trapani, Fabio; Muscolino, Giuseppe
Abstract: Artificial and natural records are commonly employed by researches and practitioners to perform refined seismic assessments of structures. The techniques for the generation of artificial records and their effectiveness in producing signals which are significantly representative of real earthquakes are still debated as well as results of the consequent seismic assessment to expect from their application. The paper presents an in-depth comparative study highlighting the effect of employing different typologies of artificial ground motion records on seismic assessment results, especially addressing seismic fragility curves. Three sets of 50 stationary, nonstationary evenly modulated and fully nonstationary accelerograms are generated based on design spectrum compatibility criteria. Standard nonlinear time history analyses of 4 reference structural models of reinforced concrete (RC) structures having different degree of complexity are firstly carried out monitoring results in terms significant engineering seismic demand parameters. So far, incremental dynamic analysis (IDA) is used to derive fragility curves. Peak ground acceleration and spectral acceleration are used as possible intensity measures in order to compare results of seismic fragility assessment. The combination of structural irregularity, severe damage and input typology is finally analyzed and discussed in order to assess the degree of dependence of fragility assessments on the typology of signal adopted. Highlights: The effect of the stationary/nonstationary input on seismic assessment is investigated. Four different structural models having different degree of complexity are analyzed. Significant seismic demand parameters are monitored comparing results. Fragility curves are derived for the 3 sets of artificial accelerograms using IDA. Dependency of IDA based fragility curves on the input typology is assessed.